ENDOCARDITIS INFECCIOSA EN EL HOSPITAL SAN JUAN DE DIOS 2000 A 2010 - Solís Solís, Luis Diego (2011)
In our country, there are few studies that assess the clinical evolution of the patients with Infective Endocarditis (IE) as well how oftenthose patients get complicated. Also, there is no clarity about the antimicrobial therapeuticschemes. A retrospective and descriptive study was performed. It was based on file revision of patients discharged with de diagnosis of IE, in the Hospital San Juan de Dios, between 2000 and 2010. The rate of complications, dead andtreatment were determined.